Konsep Visual Sistem Sarana Isyarat Penunjuk (Sign System) di Kampus Syahdan Binus University - Kartika, Rina (Bina Nusantara University, 2010)
Limited signage facilities in Syahdan Campus of Binus University, has often been the cause of the disruption of the activities of the users who are unfamiliar with the room layout in the building. Where in this case teaching and learning activities are only one of the activities conducted there, and it has to be considered that users are not only from among the faculty and students only, as regular users, but also visitors and guests as incidental users. Common problems in finding rooms that they have to go to, is usually only solved by asking someone else. Design of an effective, communicative, applicative and integrated sign system, is considered to be a solution to this problem.